2006
DOI: 10.1016/j.cplett.2006.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Matrix isolation and theoretical study on the photolysis of trichloroacetyl chloride

Abstract: UV photolysis of CCl 3 COCl has been investigated by infrared spectroscopy in cryogenic Ar and O 2 matrices. In the Ar matrix, CCl 4 and CO were found to be dominant products over Cl 2 C=C=O. The CCl 3 and COCl species, observed as intermediates, indicated C-C bond cleavage. The C-C bond cleavage was also evidenced by the formation of ClC(O)OO in the O 2 matrix. The marked difference in the photochemistry of matrix-isolated CCl 3 COCl from that of CH 3 COCl, where CH 2 =C=O is the predominant product, can be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
1
9
0
2
Order By: Relevance
“…As a result of the photolysis of O 2 upon 185.0 nm excitation, ozone was produced at 1037 cm −1 [16]. A strong band at 2342 cm −1 was assigned to CO 2  3 [17]. Unfortunately, we could not determine the reason for the absence of the peaks due to benzoyl chloride.…”
Section: Photolysis Of Cba In the Ar And O 2 Matricesmentioning
confidence: 61%
“…As a result of the photolysis of O 2 upon 185.0 nm excitation, ozone was produced at 1037 cm −1 [16]. A strong band at 2342 cm −1 was assigned to CO 2  3 [17]. Unfortunately, we could not determine the reason for the absence of the peaks due to benzoyl chloride.…”
Section: Photolysis Of Cba In the Ar And O 2 Matricesmentioning
confidence: 61%
“…In some processes the transition structures were found to be close to the products because of the very short life time of those TSs. Phospogene (COCl 2 ), dichloroketene (CCl 2 CO), Carbon dichloride (CCl 2 ), Carbon tetrachloride (CCl 4 ), and Carbon monoxide (CO) are the major dominant products on the decomposition of the trichloroacetyl chloride and these products are experimentally observable [15]. These products are found to be highly hazards than the parent trichloroacetyl chloride molecules.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, in the atmosphere at suitable condition this resultant product of trichloroacetyl chloride have probability of dissociation and rearrange to form most hazardous pollutants, such as phosgene, carbon monoxide, carbon tetrachloride, and so forth. Takumi Tamezane et al [15] previously reported that the trichloroacetyl chloride undergoes various possible reaction channels to release the major pollutants, such as carbon monoxide, carbon tetrachloride, and a minor quantity of phosgene to the atmosphere on UV irradiation. But, the detailed information to the product channels, product distributions, and reaction kinetics are still missing.…”
Section: Introductionmentioning
confidence: 99%
“…The latter band behaved as a group A band after prolonged irradiation. Ketene species and CO absorption bands are known to emerge in the ~2140 cm -1 region [14][15][16]. In fact, in the photolysis of benzoyl chloride the ketene product showed the absorption band assigned to the C=C=O asymmetric stretching vibration at 2120 cm -1 and the CO product showed the absorption band at 2138 cm -1 [6].…”
Section: Methodsmentioning
confidence: 99%